Implementation of diversion as the settlement of child criminal cases in the perspective of Islamic law - Muhammad Arafat; Asmuni (The International Journal of Politics and Sociology Research, 2022)
This research settles child crime culprits. This study uses descriptive analysis to find law enforcement authorities' diversion of child perpetrators' criminal activities, assess Law Number 11 of 2012's effectiveness, and examine Islamic law's perspective on diversion and its efficacy in settling child offender cases in Indonesia. This study found that since Law no. 11 of 2012 on the Juvenile Criminal Justice System (SPPA Law) was passed, many parties have hoped for a model of a criminal justice system that is more particular to children in Indonesia and better. As-Sulh in Islamic law and diversion in positive law. Islamic law does not criminalize children, but the leader can impose ta'dib (learning) punishments. Thus, tranquility or diversion is stressed while dealing with law-breaking youth. Juvenile crime management in Indonesia and Islamic law follows the notion of legality and emphasizing the child's interests through diversion and restorative justice.